Analysis of Clinical and Demographic Predictors of Anxiety and Depression in Rheumatoid Arthritis Patients - Herlina Yani (Indonesian Journal of Rheumatology, 2026)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease with substantial physical and psychological impact. Anxiety and depression are common comorbidities that may affect disease outcomes, but their association with disease activity remains inconsistent, particularly in Indonesia. Objective: This study aimed to analyze clinical and demographic predictors of anxiety and depression in RA patients, with emphasis on their association with disease activity measured by DAS28-CRP. Methods: A cross-sectional study was conducted on 58 RA patients at Royal Prima Hospital, Medan. Demographic and clinical variables were recorded. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS), and disease activity was measured with DAS28-CRP. Associations were tested using logistic regression, and correlations were analyzed with Spearman’s rank test. Results: The mean age was 47.9 years, and 91.4% were female. Anxiety was identified in 19.0% and depression in 17.2% of participants. High DAS28-CRP was significantly associated with anxiety (OR 5.07; 95% CI 1.26–20.37; p=0.016). In multivariate analysis, DAS28-CRP remained the strongest predictor of anxiety (AOR 3.89; p=0.073), although not statistically significant. Depression was not associated with demographic or clinical characteristics. Spearman correlation showed a positive association between DAS28-CRP and anxiety scores (r=0.304; p=0.020), while the correlation with depression was weaker and not significant. Conclusion: Anxiety, but not depression, was associated with higher disease activity in RA patients. Routine psychological screening, particularly for anxiety, should be incorporated into RA management